Mice flow routing in data centers based on software-defined networking (2018)
Network operators have used SDN for routing flows in DCNs. However, a significant problem affecting the overall performance of DCNs based on SDN is the delay introduced to latency-sensitive small flows (i.e., mice) by the SDN controllers. Current approaches tackle this problem by compiling and installing paths for mice and elephants dynamically, but this has shortcomings related to the large number of routing rules that the switches must handle, leading to significant delays to mice flows. In this monograph, we introduce MiceDCER, an algorithm that allows the efficient routing, regarding the delay, of mice flows in SDN-based DCNs by assigning internal Pseudo-MAC (PMAC) addresses to the edge switches and hosts. It also installs wildcard rules based on the information carried out by the ARP packets, to indicate the controller the rules it should install on the switches. To test our algorithm, we developed a prototype and conducted the experiments in an emulated topology to compare the results with other routing protocols based on the number of rules. This comparison reveals that MiceDCER significantly reduces the number of rules installed in switches on the topology and, therefore, contributes to reducing the delay in SDN-based DCNs.